2016
DOI: 10.1038/bjc.2016.216
|View full text |Cite
|
Sign up to set email alerts
|

Screening women for cervical cancer carcinoma with a HPV mRNA test: first results from the Venice pilot program

Abstract: Background:HPV DNA-based screening is more effective than a Pap test in preventing cervical cancer, but the test is less specific. New HPV tests have been proposed for primary screening. The HPV mRNA test showed a similar or slightly lower sensitivity than the HPV DNA tests but with a higher specificity. We report the results of an organised HPV mRNA-based screening pilot program in Venice, Italy.Methods:From October 2011 to May 2014, women aged 25–64 years were invited to undergo a HPV mRNA test (Aptima). Tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
4
13
0
Order By: Relevance
“…When we applied this value to the whole screened population, and with the assumption that HPV mRNA-positive HPV DNA-negative women are a small proportion of the screened population, ranging from 0.6% to 1.5% (7,(9)(10)(11), the positivity rate would be about 5.5 to 6.5%. Our data are consistent with those reported in other studies, ranging from 57% to 85% in HPV DNA-positive women (7,(9)(10)(11)(12) and from 4.7% to 10% in the general population (8)(9)(10)(11)(12)(13).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…When we applied this value to the whole screened population, and with the assumption that HPV mRNA-positive HPV DNA-negative women are a small proportion of the screened population, ranging from 0.6% to 1.5% (7,(9)(10)(11), the positivity rate would be about 5.5 to 6.5%. Our data are consistent with those reported in other studies, ranging from 57% to 85% in HPV DNA-positive women (7,(9)(10)(11)(12) and from 4.7% to 10% in the general population (8)(9)(10)(11)(12)(13).…”
Section: Discussionsupporting
confidence: 93%
“…The tests targeting HPV E6-E7 mRNA have been suggested both as a putative primary screening test (7,8) and as a triage test instead of cytology (9).…”
mentioning
confidence: 99%
“…Therefore, we cannot exclude that differences in terms of underlying risk of infection, previous screening, prevalence of CIN lesions could exist between the two populations, Furthermore, the histological endpoints were not assessed by the same labs and differences in the evaluation of CIN may have occurred . In fact, we previously showed that the results at first screening were quite similar as regards HPV positivity and detection of CIN2+, notwithstanding some different process indicators, such as positivity at cytology triage, which was performed by different laboratories. Nevertheless, since the present study regarded the results at rescreening of women that were negative at previous screening round, the differences in previous screening uptake have been minimized.…”
Section: Discussionmentioning
confidence: 92%
“…The projects' protocols have been previously described. 18,23 In Venice, cervical cells were collected in a Thin-Prep transport device (Hologic, San Diego, CA) suitable for both tests, while two separate samples (a conventional smear for cytological triage and a sample in Qiagen Standard Transport Medium, Qiagen, Hilden, Germany) were obtained within the HPV-DNA-based projects.…”
Section: Methodsmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] On this basis, data on the performance of HPV-based screening in a real-world clinical setting, in contrast to a randomised research setting, are beginning to emerge. 12,15,[18][19][20][21][22][23][24][25][26][27][28] However, only few of these studies compared HPV-based screening with a contemporary control group screened by cytology. 12,18,19 In Denmark, national guidelines recommend screening every 3 years in women aged 23-49 and every 5 years in women aged 50-64.…”
Section: Introductionmentioning
confidence: 99%